Spatial Analysis for Habitat Estimation of the Sumatran Chestnut-necklaced Partridge Tropicoperdix charltonii atjenensis (Galliformes: Phasianidae) in Aceh, Sumatra, Indonesia - Wahyudi, Tedi; Radinal; Kiswayadi , Dedi (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Kepustakaan, 2025)
The Sumatran Chestnut-necklaced Partridge Tropicoperdix charltonii atjenensis is a subspecies endemic to the lowland forests of Aceh and Lampung, Sumatra. This study used the Analytical Hierarchy Process (AHP) to identify suitable habitats for this subspecies, considering environmental variables such as elevation, tree cover, slope, distance to water sources, and anthropogenic factors. Data collection and spatial analysis were conducted from July 22 to August 23, 2023. The AHP analysis revealed that T. c. atjenensis is typically found in lowland habitats with specific characteristics: average elevation of 130 meters, proximity to water sources, and very dense forest cover (93%). Additionally, suitable habitats tend to be far from road access (average distance of 1.7 km) and residential settlements (average distance of 5.3 km). The resulting distribution map highlights the importance of well-preserved, forested areas as primary habitats for this subspecies.